Case Report: A Young Man With Giant Pericardial Synovial Sarcoma - Luo, Yong; Gong, Ke; Xie, Ting; Liu, Ruilin; Guo, Hui; Wang, Lei; Tan, Zhiping; Hu, Shi jun; Yang, Yifeng; Xie, Li (Frontiers in Cardiovascular Medicine, 2022)
Pericardial synovial sarcomas are sporadic tumors. Herein, we report a case of primary pericardial synovial sarcoma originating from the right pericardium. Missed diagnosis delayed surgical treatment. Eventually, the tumor occupied the almost entire pericardial cavity. The pericardial tumor was surgically removed as soon as possible after admission. In this paper, we aim to provide details that can help further understand the differing symptoms and presentations of pericardial synovial sarcoma and highlight the importance of consideration of this disease in similar cases where the etiology of pericardial effusion is unknown.